Assessing adaptation options for climate change: A guide for coastal communities in the Coral Triangle of the Pacific 7. Ecosystem Services Mapping. - WorldFish (2013)
Assessing options for adapting to climate change is an important part of building resilient fishing and farming communities. This brochure is part of a series that collectively detail how a community-based assessment of climate change was used in partnership with coastal communities and provincial and national-level stakeholders in Timor-Leste and Solomon Islands. The assessment contains four distinct, but related, steps (Fig 1) focused on supporting community-level decision-making for adaptation through a series of participatory action research activities. Each brochure in this series details a specific activity in the four-step assessment. This series of eight brochures is primarily aimed for use where resources are limited or where it is more appropriate to use a rapid, qualitative and non-data intensive method of assessment. Community leaders, local NGOs and regional and national-level government representatives in developing countries may find this series useful. In this brochure we provide details of an activity relating to the ‘Evaluation of options’ step of the assessment. This activity involves working with provincial and national-level stakeholders to produce an annotated map of the natural resources that provide essential ecological services needed to underpin fishing and farming livelihoods. Ecosystem services are the benefits that people obtain from ecosystems, such as nutrient cycling and fresh water (Fig 2). The activity generally aims to provide an understanding of the following questions: • What are the main land uses, coastal resources and natural resource components that contribute to the ecosystem services needed to underpin fishing and farming livelihoods? • Which natural resource components do communities value? • What are the likely impacts of a change in the condition, use, or management of natural resources on the ecosystem services they provide?